Characterisation of lesions and associated immune cell populations in the lung of African buffalo (Syncerus cafe) infected with Mycobacterium Boris - Goldswain, Samantha (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.